Efficient anti-tumor nano-lipoplexes with unsaturated or saturated lipid induce differential genotoxic effects in mice. Issue 9 (21st October 2019) - Rachamalla, Hari Krishnareddy; Mondal, Sujan Kumar; Deshpande, Shruti S.; Sridharan, Kathyayani; Javaji, Kalpana; Jaggarapu, Madan Mohan Chandra Sekhar; Jinka, Sudhakar; Bollu, Vishnusravan; Misra, Sunil; Banerjee, Rajkumar
Abstract: Cationic lipids are well-known excipients for nanometric liposomal gene delivery systems. However, because of the suspected, collateral toxicity in normal cells, the use of cationic lipids for the treatment of human tumor is largely limited. Recently, we developed a glucocorticoid receptor (GR)-targeted liposomal, anticancer delivery system (DXE nano-lipoplex), which carried cationic lipid of saturated twin aliphatic chains. It exhibited efficient anti-tumor effect in aggressive and drug-resistant tumor models. Toward exploring lipoplex's human clinical use, we incorporated another nano-lipoplex (D1XE) group that carried cationic lipid with one of its aliphatic chain carrying unsaturation and compared in vivo genotoxicological profiling-based safety assessment and the respective anti-tumor efficacy of the lipoplexes. Thus, both the lipoplexes differ only by the chemical identity of one of their constituent cationic lipid. Unsaturated aliphatic chains in lipid generally impart efficient cell surface fusogenic property in lipid formulations. Herein, we report that nanoplex with unsaturated cationic lipid (D1XE) exhibited better physical appearance with less flocculent behavior than nanoplex with saturated lipid (DXE). Upon multiple injections, D1XE nanoplex imparted better tumor regression but most importantly, exhibited much lower overall toxicity (e.g. genotoxicity, weight loss, etc.) than DXE nanoplex. With a higher antitumor effect but a lower genotoxic effect, D1XE is proved to be a better nanoplex than DXE for the potential clinical trial. Thus, this study clearly delineates the importance of incorporating a constituent lipid that carries a single unsaturated aliphatic chain toward developing efficient anti-tumor nano-lipoplexes with reduced genotoxicity.